African Debt since HIPC : How Clean is the Slate? - Merotto, Dino (World Bank, Washington, DC, 2015)
The paper finds a moderate evolution in public debt ratios since debt relief among heavily indebted poor countries (HIPC) and multilateral debt relief initiative (MDRI) recipient countries in Sub-Saharan Africa, with certain exceptions. For eight countries the authors find rapid rates of debt accumulation, which can return them to pre-HIPC debt levels in only a few years. Short-term domestic debt has, despite early fears, in general not filled the borrowing space created by debt relief. However, external debt accumulation on commercial terms in some cases presages repayment spikes, which may combine with short-term domestic obligations to amplify refinancing risk and cause abrupt reductions in public spending, with damaging consequences for development. Finally, despite reduced debt, African economies continue to be commodity dependent and prone to shocks. As global interest rates and commodity prices revert to historically more customary levels, these countries should remain prudent: avoid tax-base erosion, prevent large recurrent spending hikes, and invest wisely in growth, by executing projects effectively to enhance infrastructure. These fiscal fundamentals will be as important for debt sustainability as how much is borrowed and on which terms.